STUDI TENTANG TEKNIK, BENTUK, WARNA, DAN MOTIF PRODUK KERAJINAN LAKUER PALEMBANG SUMATERA SELATAN - FEBRI YANTO, Drs. Yusron Wikarya, M.Pd. Drs. Erwin A, M.Sn. (Universitas Negeri Padang, 2016)
This study aims to describe. Technique 1); product forms 2); color 3); and motive 4); lakuer craft to be more known to the public and the younger generation of local, national, and global. The method used is qualitative method with descriptive approach. Sources of data obtained from informants in the form of products sold in the written records, audio recordings, vidio, photographs, and literature study. Data were analyzed with qualitative analysis. The results showed that lakuer craft technique consists of, namely: Preparation tools and materials, workmanship Stage. Lakuer craft form is divided into: astigmatism / lathe, Cube, Miniature. Lakuer color maroon, yellow, black. Lakuer motifs derived from forms of flora, fauna and geometric.Keywords: Engineering, Shape, Color, Motif Craft Lakuer Palembang